2019
DOI: 10.4103/aam.aam_22_18
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the efficacy of intravenous benzylpenicillin and intravenous augmentin in the empirical management of Ludwig's angina

Abstract: Background: Ludwig's angina is a potentially life-threatening condition characterized by bilateral cellulitis of the submandibular, submental, and sublingual spaces. Intravenous (I.V) penicillin G or amoxicillin-clavulanate (Augmentin) has been recommended for use as empirical management before obtaining culture and sensitivity results. Aim: The aim of this study was to compare the therapeutic efficacies and clinical outcomes of I.V benzylpenicillin with I.V Augmentin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…Baomah et al compared co-amoxiclav with benzyl penicillin in the treatment of Ludwigs angina in Ghana, and found that both these drugs are equally effective. 18 Agweyu et al compared oral amoxycillin with benzyl penicillin in Kenyan children with severe pneumonia and found no difference in their efficacy. 19 Atkinson et al compared oral amoxicillin with intravenous benzyl penicillin in patients of community-acquired pneumonia, and found equal efficacy of these two pharmacologic agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baomah et al compared co-amoxiclav with benzyl penicillin in the treatment of Ludwigs angina in Ghana, and found that both these drugs are equally effective. 18 Agweyu et al compared oral amoxycillin with benzyl penicillin in Kenyan children with severe pneumonia and found no difference in their efficacy. 19 Atkinson et al compared oral amoxicillin with intravenous benzyl penicillin in patients of community-acquired pneumonia, and found equal efficacy of these two pharmacologic agents.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Thus, there is significant difference of prices between the two drugs with similar efficacy and safety profile. 18…”
Section: Discussionmentioning
confidence: 99%
“…Outros fatores que podem comprometer o estado imunológico do paciente podem estar relacionados, a exemplo de diabetes melitus, quimioterapia antineoplásica, infecção pelo vírus da imunodeficiência humana, gravidez, puerpério, alcoolismo, desnutrição crônica, baixo nível socioeconômico, insuficiência renal, cirrose hepática, anemia, hipertensão arterial sistêmica, obesidade, doença tireoidiana 10,11,12 .…”
Section: Referencial Teóricounclassified
“…Em casos graves, pode haver dispneia 2,11 , ruptura da artéria carótida ou abscesso da bainha, tromboflebite da veia jugular interna, mediastinite, empiema, fasciite necrotizante, derrame pericárdico, osteomielite e septicemia 4,10 , infecções do globo ocular e abscessos cerebrais 1 . É preciso atentar para o fato de que algumas manifestações podem estar mascaradas pelo uso indevido de antibióticos e que os sintomas podem progredir rapidamente; sendo, portanto, fundamental buscar atendimento especializado imediato ciência plural…”
Section: Referencial Teóricounclassified